Burnout in familial caregivers of patients with dementia - Truzzi,Annibal (2012)
OBJECTIVES: Familial caregivers of demented patients suffer from high levels of burden of care, but the literature is sparse regarding the prevalence and predictors of burnout in this group. Burnout is composed of three dimensions: emotional exhaustion (EE), depersonalization (DP) and reduced personal accomplishment (RPA). We aimed to investigate the associations between burnout dimensions and the caregivers' and patients' sociodemographic and clinical characteristics. METHODS: This study is cross-sectional in design. Caregivers (N = 145) answered the Maslach Burnout Inventory, Beck Depression Inventory, Beck Anxiety Inventory and a Sociodemographic Questionnaire. Patients (N = 145) were assessed with the Mini Mental State Examination, Functional Activities Questionnaire, Neuropsychiatric Inventory, and Clinical Dementia Rating Scale. RESULTS: High levels of EE were present in 42.1% of our sample, and DP was found in 22.8%. RPA was present in 38.6% of the caregivers. The caregivers' depression and the patients' delusions remained the significant predictors of EE. CONCLUSIONS: The presence of caregiver depression and patient delusions should always be part of the multidisciplinary evaluation of dementia cases.